Infrared Thermography for Non-Destructive Testing of Cooling Hole Integrity and Flow Evaluation in Specimens Made with Innovative Technologies - Ester D’Accardi; Luca Ammannato; Alessandra Giannasi; Marco Pieri; Giuseppe Masciopinto; Francesco Ancona; Giovanni Santonicola; Davide Palumbo; Umberto Galietti (Engineering Proceedings, 2025)
This study developed a non-destructive testing (NDT) method using infrared thermography to inspect tubes with holes and slots made by electro-erosion and additive manufacturing. CO2 was used as a tracer gas to verify the opening and evaluate the flow shape from the holes and slots. To improve the signal contrast, a controlled hot background was used as a reference, and infrared cameras monitored the thermal response to detect flow variations caused by different geometries. The tests included different diameters, pitches, and aspect ratios, comparing results between additive manufacturing and electro-erosion under various conditions. Moreover, a preliminary setup using compressed air and inductive heating was developed to assess hole openings by cooling the piece, aiming to eliminate CO2 use. The comparison of results, the post-processing analysis of quantitative indices, and specific thermal features enabled a non-destructive evaluation of the holes by using different technologies, providing an assessment of the opening conditions, outlet, geometry, and flow shape.